Analisis Efisiensi Modal Kerja Terhadap Pertumbuhan Laba Pada PT. Kawasan Industri Makassar (Persero) ( PT. Kima Makassar ) - Chindi Lainora; Sabirin Iskandar; Abdullah Abdullah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research aims to determine whether the company's working capital has shown efficiency in increasing better profit growth. The author's research object is PT. Makassar Industrial Zone (Persero). This research method is descriptive research using quantitative methods. Quantitative data is numerical data, data obtained from financial reports. Researchers use data collection techniques accompanied by documentation. The results of the research show that the efficiency ratio shows the turnover of fixed assets that are sold a lot so that the turnover of receivables increases so that profitability can increase profit growth. So it is concluded that profit growth at PT. Makassar Industrial Zone (Persero) working capital management has not been shown to be efficient.